49 'Pic' your patient: development of a multi-professional handover tool. Issue 3 (1st September 2017) - Chapman, Laura; Mills, Mark; Robinson, Claire
Abstract : Background: In a 26 bedded hospice, handovers were excessive and inefficient. Our review revealed over 15 handovers per day between different professionals. The Multi-disciplinary team (MDT) felt frustrated, recognising handovers reduced time for direct patient contact without ensuring timely sharing of crucial information. Staff wanted a single, efficient MDT handover to identify key patient issues. Method: Current available tools were reviewed including SBAR 1 (Situation, Background, Assessment, and Recommendation) but were unsuitable for the hospice. The PIC acronym was created to facilitate nursing presentation of each patient. This prompted discussion of: Plan (Is the patient going anywhere today? Are we planning discharge to their preferred place of care?); Involvement (Are appropriate MDT members involved?); Concerns (Are there any patient or family concerns?). The PIC tool was used at the newly launched 'Huddle' – a handover led by a senior nurse and designated consultant, with a representative from each discipline of the MDT occurring each weekday morning. Results: Informal feedback from staff suggested the Huddle and PIC tool enabled more efficient discharges. It was useful to view the complexity of the patients throughout the hospice and guide admissions. A formal survey of the MDT is being carried out, with results available by October 2017. Conclusion: Huddle is reducing the number of handovers each day and increasing the productivity of the hospice. This has benefits for swift discharge and assessing the needs of patients with complex problems. An unintended benefit has been improved nursing confidence in their presenting skills. Reference: . Haig K, Sutton S, Whittington J. SBAR: A shared mental model for improving communication between clinicians. The Joint Commission Journal on Quality and Patient Safety 2006;32(3):167–175